108 PHEOCHROMOCYTOMA-INDUCED CARDIOGENIC SHOCK: A MULTICENTRE ANALYSIS OF CLINICAL PROFILES, MANAGEMENT AND OUTCOMES. (15th December 2022) - Angelis, Elena De; Bochaton, Thomas; Ammirati, Enrico; Tedeschi, Andrea; Polito, Maria Vincenza; Pieroni, Maurizio; Merlo, Marco; Van De Heyning, Caroline M; Cipriani, Alberto; Camilli, Massimiliano; Sanna, Tommaso; Cabassi, Aderville; et al.
Abstract: Aims: There is still uncertainty on the management of patients with pheochromocytoma-induced CS (PICS), as only a few clinical cases have been reported. The aim of this study is to investigate the clinical presentation, management, and outcome of patients with PICS. Methods: We collected retrospectively 18 patients without previously known pheochromocytoma with histologically proven PICS admitted to 8 European hospitals. Results: Among the 18 patients with a mean age of 50 years, 50% were men. The main clinical features at presentation were pulmonary congestion (83%) and cyclic fluctuation of hypertension crises and hypotension (72%). On echocardiography, mean left ventricular ejection fraction (LVEF) was 25% with an atypical-Takotsubo pattern (basal/midventricular) in 50%. Laboratory exams showed increased inflammatory markers, in particular, the mean white blood count was 21.9*10 9 /L. Inotropes/vasopressors were started in all patients and a temporary mechanical circulatory support (t-MCS) was required in 11 (61.1%) patients. All patients underwent surgical removal of the pheochromocytoma but 4 (22.2%) on t-MCS. Echocardiogram (16/17 patients) revealed a mean LVEF of 55% at discharge. Only one patient required heart transplantation (5.5%), and all patients were alive at a median follow-up of 679 days. Conclusions: In patients with PICS, characteristically, an atypical Takotsubo pattern was observed in almost half of the cases. Although the use of exogenous catecholamine can be perceived as deleterious, we showed a fairly good mid-term prognosis with rapid improvement of LVEF in most, even if adrenalectomy often occurred on t-MCS.